Master and Servant: Emerging Roles for Motor Neuron Subtypes in the Construction and Evolution of Locomotor Circuits - Dasen, Jeremy S. (Curr Opin Neurobiol, 2016)
Execution of motor behaviors relies on the ability of circuits within the nervous system to engage functionally relevant subtypes of spinal motor neurons. While much attention has been given to the role of networks of spinal interneurons on setting the rhythm and pattern of output from locomotor circuits, recent studies suggest that motor neurons themselves can exert an instructive role in shaping the wiring and functional properties of locomotor networks. Alteration in the distribution of motor neuron subtypes also appears to have contributed to evolutionary transitions in the locomotor strategies used by land vertebrates. This review describes emerging evidence that motor neuron-derived cues can have a profound influence on the organization, wiring, and evolutionary diversification of locomotor circuits.